Customer lifetime value drivers of independent retailers within South Africa's informal trade environment: an empirical case study - Msibi, Balekile Catherine (My University, 2021)
Customer Lifetime Value (CLV) is a “technique for analysing all the potential value purchase values from a single customer over the lifetime of a relationship with a supplier or service provider” (Doyle, 2016). It is a valuable measure that can be used to segment customers according to their profitability in order to implement customer-focused marketing strategies. The study looks at independent retailers that operate within the informal trade environment and are directly serviced by a consumer packaged goods (CPG) company within the snacking category. Through the analysis of these customers, this study aims to provide empirical evidence to support the utilisation of CLV as a customer segmentation tool within a businessto-business (B2B) setting based on CLV drivers. This study also seeks to understand whether short-term macroeconomic indicators such as inflation do indeed have an effect on CLV. Through the use of the Venkatesan-Kumar method for calculating CLV as well as classification trees, the study aims to create a decision rule process whose end result will be a CLV classification system. The results will equip companies with the tools and ability to identify which customer segment a customer belongs to in order to ensure that they use the appropriate customer relationship management strategies to drive customer development and retention
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management in Strategic Marketing to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2021
Keywords: Customer equity; Customer lifetime value; Classification and regression trees; UCTD; SDG-8: Decent work and economic growth